Chapter 2 WeChat as migration infrastructure The case of Chinese-Russian precarious labour markets - Ryzhova, Natalia (Taylor & Francis, 2022)
This chapter focuses on one Russian province, the Irkutsk Oblast, which due to its location has become a trans-shipment point for legal and illegal migration of the Chinese, as well as a place of their settling, permanent residence and business activities. It asks how new social networks, namely WeChat, help to attract Chinese workers. Using the concept of migration infrastructure, the chapter accounts for the features of the WeChat social organisation, which prevents the political/social integration of the diaspora in general, but strengthens informal practices and, most importantly, 'containerises' the flow of Chinese labour.